2009
DOI: 10.2209/tdcpublication.50.117
|View full text |Cite
|
Sign up to set email alerts
|

Soft-diet Feeding Inhibits Adult Neurogenesis in Hippocampus of Mice

Abstract: Our previous study showed that mice fed on a soft diet after weaning had reduced levels of brain-derived neurotrophic factor (BDNF) protein in the hippocampus after 3 months of age compared with mice fed on a hard diet. BDNF is one of the most effective promoters of neurogenesis in the hippocampus, and enhancement of BDNF production has been shown to enhance neural precursor cell proliferation in the dentate gyrus. We hypothesized that soft-diet feeding during development would reduce the proliferation rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 26 publications
2
24
0
5
Order By: Relevance
“…Brain-derived neurotrophic factor (BDNF) is one of the many signaling molecules involved in regulating AHN [14,18]. Interestingly, it has been demonstrated in studies that soft-diet feeding in mice leads to altered expression of BDNF and its receptor, Tryosine receptor kinase B (TrkB), in the hippocampus and restrained AHN, which resulted in behavioral impairments [12,19]. Impairment of this process results in impaired memory function, and studies involving ablation of these neurons demonstrates this.…”
Section: Adult Hippocampal Neurogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Brain-derived neurotrophic factor (BDNF) is one of the many signaling molecules involved in regulating AHN [14,18]. Interestingly, it has been demonstrated in studies that soft-diet feeding in mice leads to altered expression of BDNF and its receptor, Tryosine receptor kinase B (TrkB), in the hippocampus and restrained AHN, which resulted in behavioral impairments [12,19]. Impairment of this process results in impaired memory function, and studies involving ablation of these neurons demonstrates this.…”
Section: Adult Hippocampal Neurogenesismentioning
confidence: 99%
“…The loss of teeth has also been suggested to be related to the development of senile dementia and Alzheimer's disease [9], with both conditions featuring loss of memory function and disturbed learning, areas that AHN has been hypothesised to modulate [4]. Several studies have investigated whether masticatory impairment affects AHN in mice and rat models, such as through soft-diet feeding (not requiring mastication) [10] and removal of molars [11] with another study demonstrating that a soft-diet in mice after weaning resulted in impaired AHN in later life [12]. A review of the relationship between mastication and dementia surmised that a correlation does indeed exist [13].…”
Section: Introductionmentioning
confidence: 99%
“…After comparing the cell proliferation in DG of adult mice fed on hard and soft diet, Yamamoto et al (Yamamoto et al, 2009) found that sufficient mastication activity enhanced hippocampal neurogenesis since that the total number of BrdU-labeled cells was fewer in the soft-diet group than in the hard-diet group at 3 and 6 months of age.…”
Section: Othersmentioning
confidence: 99%
“…This product of the NTRK gene is expressed in several types of cells and tissues with major expression in neural cells and cardiomyocytes [4]. BDNF exerts several effects in the central nervous system: it regulates the development and differentiation of new neurons [5][6][7] and promotes neuron survival [8][9][10]; it influences mood and depression [11][12][13]; it controls sleep [14] and modulates appetite [15,16]. In addition, alterations in BDNF have been identified in various chronic neurodegenerative diseases [17].…”
Section: Introductionmentioning
confidence: 99%